Biological control of bacteria wilt in tobacco caused by Ralstonia solanacearum - Terblanche, Johanna Dina (University of the Free State, 2007)
The phase out of well-known chemical control products, especially soil fumigants, is a reality and biological control strategies need to be explored. Biological control rarely eliminates a pathogen from the soil, usually it reduces its numbers or ability to induce disease. However combining complementary biological control tactics may become the only tool in integrated control management for soilborne diseases. The biggest challenge will be to determine the most feasible sequence of techniques for optimal control of each pathogen, farming system and geographic area. Other factors that may have an influence on the efficacy of any bio-control strategy are host related (genetic resistance), environment related (longevity. soil type & climate) and pathogen related (virulence, inoculum density, survival). There is considerable interest in biofumigation as an alternative to synthetic soil fumigants in horticulture and agriculture. The term biofumigation usually referrers to the biocidal effects of isothiocyanates (ITC’s) released from Brassicaceous plants. It can and should however be extended to other volatile bio-substances with the same qualities like thiophene, a heterocyclic, sulphurous compound released by Tagetes spp. The rhizosphere presents a complex integrated ecosystem. Biotic and abiotic factors present, can determine the dynamics and structure of the microbial population in a specific rhizosphere. Screening different crops for rhizosphere suppression of soilborne pathogens can be a point of departure to select crops for a specific crop rotation system. A series of summer- and winter crops were evaluated for rhizosphere suppression of Ralstonia solanacearum (Race 1, Biovar III), causal agent of bacterial wilt in tobacco. Ocimum basilicum (sweet basil), Tagetes erecta (giant marigold), T. patula (dwarf marigolds), Coriandrum sativum L. (coriander) and Triticum aestivum L. (wheat cv. Inia) resulted in a significant control of the pathogen. However all Tagetes spp.had the lowest pathogen population count of all crops evaluated. A greenhouse trial conducted in 0,5 m deep soil indicated that the T. patula in combination with non-host winter crops, could reduce the pathogen population of the soil to such an extent that the disease incidence on the followup tobacco crop was 40% lower than that of the initial tobacco crop. A four-year rotation trial on a heavily infested field showed that T. patula in combination with wheat was responsible for a significantly higher tobacco yield (green leaf mass). In both greenhouse and field trials, cabbage (Brassica oleracea L. var capitata.) proved to be a latent host, suggesting that it should be avoided as a winter cash crop in tobacco fields infested with R. solanacearum.
Keywords: Dissertation (M.Sc. (Plant Sciences, Centre for Plant Health Management))--University of the Free State, 2007; Tobacco -- Diseases and pests; Wilt diseases; Plant parasites -- Biological control